Motherhood and War International Perspectives - Cooper, D.; Cooper, D.; Phelan, C.; Phelan, C. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Traditional histories of war have typically explored masculine narratives of military and political action, leaving private, domestic life relatively unstudied. This volume expands our understanding by looking at the relationships between mothers and children, and the varied roles both have assumed during periods of armed conflict.